2020
DOI: 10.3390/su12198200
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of Startups in the EU—A Comparative Study

Abstract: The paper focuses on key success factors of startups in the European Union. Startup companies have a massive potential to boost the level of innovation and competitiveness of national economies. They are also uniquely equipped to provide extremely effective and flexible ways of meeting both existing and emerging market needs. However, the development of these microventures differs from country to country. Hence, we put forth a hypothesis that strategic success factors in the development of startups vary in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…The results confirm the importance of human and financial resources in the creation of start-ups described in the references [8,12,18,40,43,46]. In Polish cities, resource conditions have the strongest impact on the development of this form of entrepreneurship.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results confirm the importance of human and financial resources in the creation of start-ups described in the references [8,12,18,40,43,46]. In Polish cities, resource conditions have the strongest impact on the development of this form of entrepreneurship.…”
Section: Discussionsupporting
confidence: 84%
“…They also become the basis for a more dynamic local development by attracting new sectoral investors and creating new jobs. In a long-term perspective, well-functioning start-ups contribute to the increase in income levels of the local community and improve the quality of life in the region [6][7][8]. Previous research also suggests that the initiation and development of start-ups-in addition to strengthening entrepreneurship-contributes to increased resilience to external threats, including those related to pandemics [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using partial least squares structural equation modeling, this study showed that entrepreneurial push strategies in universities does not account for differences in the students' entrepreneurial intentions. Last, even though they did not discuss universities, Eulalia and Romuald [33] examined success factors of start-ups in the European Union. Emphasizing that it is imperative for start-up companies to boost innovation levels, the competitiveness of national economies also needs to be considered as a factor impacting sustainability [34], this study determined the key success factors of start-ups in the EU and classified the gap between developed and lagging member states.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the dynamic development of intellectual potential, it is necessary to create appropriate organisational and economic conditions (resources). The experience of leading countries with innovative economies (e.g., USA, Germany, Japan, Australia, Canada, Sweden, Finland and others) shows that the following elements act as organisational and economic foundations: the functioning of universities of research and business type; the functioning of business incubators and science and technology parks; personnel policy at enterprises, focused on the development of the quality of human resources; an effective migration policy focused on attracting high-quality human resources (Skawińska and Zalewski, 2020). In many technologically developed countries, one of the key roles in terms of forming intellectual potential belongs to research and entrepreneurial institutions of higher educational, where fundamental and applied research and entrepreneurial developments for commercialisation are concentrated (Amuda, 2020).…”
Section: Introductionmentioning
confidence: 99%